Analysis of Intermediate Casing Wear in Ultra-deep Wells in China's Tarim Oil Field. Issue 1 (April 2021) - Ma, Chao; Gao, Baokui; Wang, Jieli; Hu, Tianxiang; Chen, Xingwang
Abstract: Intermediate casing wear with a spiral scar is often found in ultra-deep wells in Tarim Oil Field. In this work, the mechanism of such wear, and the measures to reduce wear are analyzed. Comparing the geometric characteristics of the wear scars, the root cause is found that the effective inner diameter of the casing is smaller than the outer diameter of the drill pipe joint after the uncemented casing helically buckled. To analyze the main factors affecting the helical buckling of the casing, the classical pipe mechanics theory is used and Well-X in Tarim area is taken as an example. The results show that too small hanging weight is the main cause of helical buckling of the casing. Besides downhole high temperature and large hole diameter enlargement rate are also important factors. The main measures, such as increasing the hanging weight, installing centralizers, and using graded cementation, have been proposed to reduce wear.